2009
DOI: 10.1016/j.tsf.2009.02.055
|View full text |Cite
|
Sign up to set email alerts
|

Thermal dependence of low-frequency noise in polysilicon thin film transistors

Abstract: Thermal dependence of low frequency noise in low temperature (600°C) polysilicon thin film transistors is studied in devices biased from weak to moderate inversion and operating in the linear mode. Drain current noise spectral density, measured in the temperature range from 260K to 310K, is thermally activated following the Meyer Neldel rule. Analysis of the thermal activation of noise, supported by the theory of trapping/detrapping processes of carriers into oxide traps located close to the interface, leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Third, the lowfrequency noise in MOS transistors is higher than the noise in BJTs, as one can see in Figure 15. In this figure, the data are for 134 nMOS transistors from [22,47,48,49,50,51,72,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123], and for 53 pMOS transistors from [47,52,86,…”
Section: Noise In Mos Transistorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the lowfrequency noise in MOS transistors is higher than the noise in BJTs, as one can see in Figure 15. In this figure, the data are for 134 nMOS transistors from [22,47,48,49,50,51,72,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123], and for 53 pMOS transistors from [47,52,86,…”
Section: Noise In Mos Transistorsmentioning
confidence: 99%
“…Input-referred voltage noise S V G (gate voltage 1/f noise at 1Hz) in silicon MOS transistors compared to the corresponding S V B in silicon npn BJTs. ( ) for nMOS transistors from[22,47,48,49,50,51,72,82,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123], ( ) for pMOS transistors from[47,52,…”
mentioning
confidence: 99%
“…By considering the tunneling theory of carriers into the gate oxide traps located close to the interface and the following trapping/de-trapping processes, the corresponding localized states distribution N T can be expressed by 10,20 :…”
Section: Analysis Of Low Frequency Noise Characteristics In P-type Pomentioning
confidence: 99%
“…Previous experimental studies 17,18 reported that the static drain current I DS and the 1 / f noise drain current spectral S IDS , for TFTs biased from weak to strong inversion ͑i.e., from sub-to above-threshold region͒, are thermally activated both following the empirical MN rule 8 according to…”
Section: A Temperature Dependencementioning
confidence: 99%